Outcome in patient-specific PEEK cranioplasty: A two-center cohort study of 40 implants. Issue 9 (September 2016) - Jonkergouw, J.; van de Vijfeijken, S.E.C.M.; Nout, E.; Theys, T.; Van de Casteele, E.; Folkersma, H.; Depauw, P.R.A.M.; Becking, A.G.
Abstract: Objective: The best material choice for cranioplasty following craniectomy remains a subject to discussion. Complication rates after cranioplasty tend to be high. Computer-assisted 3-dimensional modelling of polyetheretherketone (PEEK) was recently introduced for cranial reconstruction. The aim of this study was to evaluate patient- and surgery-related characteristics and risk factors that predispose patients to cranioplasty complications. Material and methods: This retrospective study included a total of 40 cranial PEEK implants in 38 patients, performed at two reference centers in the Netherlands from 2011 to 2014. Complications were registered and patient- and surgery-related data were carefully analysed. Results: The overall complication rate of PEEK cranioplasty was 28%. Complications included infection (13 %), postoperative haematoma (10 %), cerebrospinal fluid leak (2.5 %) and wound-related problems (2.5 %). All postoperative infections required removal of the implant. Nonetheless removed implants could be successfully re-used after re-sterilization. Conclusion: Although overall complication rates after PEEK cranioplasty remain high, outcomes are satisfactory, as our results compare favourably to recent literature reports on cranial vault reconstruction.